2018
DOI: 10.1177/1091581817752405
|View full text |Cite
|
Sign up to set email alerts
|

Accessible miRNAs as Novel Toxicity Biomarkers

Abstract: Novel tissue injury biomarkers have recently been identified that outperform or add value to the conventional safety biomarkers. These novel biomarkers have enhanced sensitivity and/or specificity in monitoring drug-induced tissue injury in a variety of tissues, included liver, kidney, and skeletal muscle. Among these novel biomarkers, microRNAs (miRNAs) are one type in particular that have received much attention in recent years. These microRNAs are short, endogenous noncoding nucleic acids that are involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Indeed, we found that the most upregulated miRNAs by THS in our study are likely not only involved in organ damage as liver injury (miR-151a-5p), brain injury (miR-135b-5p), and cardiac injury (miR-199a-5p) but there are also miRNAs in this group which are reported to be involved in processes related to ER stress (miR-663a, miR-215-5p) and UPR activities such as cell survival (miR-346) (references are indicated in Supplementary Table 1). Considering the marked release of the miRNAs upon THS, we also assume that the miRNA profile obtained may not only reflect regulation of ER stress and organ injury but also possible cellular disruption followed by a passive release of miRNA into the bloodstream, which was previously observed during drug-induced organ damage (46,47). Furthermore, the upregulation of miR-24-3p (log 2 fold change = 1.79) observed here in the animals subjected to THS (p < 0.001) concurs with the overexpression of miR-24-3p reported in trauma patients associated with trauma-induced coagulopathy by preventing the production of coagulation Factor X (42).…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, we found that the most upregulated miRNAs by THS in our study are likely not only involved in organ damage as liver injury (miR-151a-5p), brain injury (miR-135b-5p), and cardiac injury (miR-199a-5p) but there are also miRNAs in this group which are reported to be involved in processes related to ER stress (miR-663a, miR-215-5p) and UPR activities such as cell survival (miR-346) (references are indicated in Supplementary Table 1). Considering the marked release of the miRNAs upon THS, we also assume that the miRNA profile obtained may not only reflect regulation of ER stress and organ injury but also possible cellular disruption followed by a passive release of miRNA into the bloodstream, which was previously observed during drug-induced organ damage (46,47). Furthermore, the upregulation of miR-24-3p (log 2 fold change = 1.79) observed here in the animals subjected to THS (p < 0.001) concurs with the overexpression of miR-24-3p reported in trauma patients associated with trauma-induced coagulopathy by preventing the production of coagulation Factor X (42).…”
Section: Discussionmentioning
confidence: 87%
“…This issue may be solved by use of panels of multiple miRs, with miR panel profiles having potential to reflect the type of liver injury, such as differentiating between acute or chronic and hepatocellular or cholestatic phenotypes (Yamaura et al 2012). Glaab et al (2018) demonstrated liver-specific (-122, -192) and muscle-specific (-1, -133a/b, -206) miRs outperformed, in terms of sensitivity and specificity, ALT and AST in monitoring the liver and AST and CK for monitoring skeletal muscle for drug-induced injury. The biomarkers were also able to sensitively monitor bile duct injury (necrosis and hyperplasia) seen with ANIT, methapyrilene and phalloidin.…”
Section: Mechanistic and Prognostic Capability Of Mirsmentioning
confidence: 99%
“…Table 1 Biofluid-detectable miRs that are altered by toxicants in different organs. Adapted from (Schraml et al 2017;Laterza et al 2009;Wang et al 2009;Saikumar et al 2012;Haghikia et al 2012;Yokoi and Nakajima 2013;Nassirpour et al 2014Nassirpour et al , 2015Ogata et al 2015;Nishimura et al 2015;Piegari et al 2016;Raitoharju et al 2016;Bergman et al 2016;Koenig et al 2016;Yan and Jiao 2016;Rouse et al 2017;Bailey and Glaab 2018;Huang et al 2018;Bailey et al 2019;Erdos et al 2020). The number of targets from miRTarBase to some of the miRs are shown in parentheses.…”
Section: Mechanistic and Prognostic Capability Of Mirsmentioning
confidence: 99%
“…Thus, because miRNAs are readily accessible in biofluids, exhibit tissue-specific expression, and are often conserved across species, they are attractive candidates as translatable safety biomarkers for monitoring organ-specific toxicities. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Thus, because miRNAs are readily accessible in biofluids, exhibit tissue-specific expression, and are often conserved across species, they are attractive candidates as translatable safety biomarkers for monitoring organ-specific toxicities. 13,14 One of the first demonstrations of using an miRNA as a tissue injury marker was miR-122 in acetaminophen-induced liver injury. 15 Since then, a large body of literature has reported several candidate miRNAs to detect drug-induced tissue injury and/or disease in rodents and humans; for example, miR-216a in pancreatic injury, miR-21 in kidney injury, and miR-499 in acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%